Comparison of API and Minitek to Center for Disease Control methods for the biochemical characterization of anaerobes. - Hansen, S L (1976)
Two commercially available micromethod multitest systems (API, Analytab Products, Inc., Minitek-Bioquest) were compared with conventional tests suggested by the Center for Disease Control for the identification of anaerobes. Anaerobiosis for the microsystems was achieved using GasPak system (BBL), A total of 175 anaerobes, including 158 clinical isolates and 17 reference strains, were used. Gram morphology, gas-liquid chromatography data, and biochemical reactions from the Center for Disease Control and Virginia Polytechnic Institute anaerobic manuals were used to identify the organisms. The Minitek system included a new anaerobe inoculum broth and two new disks, dextrose without nitrate and nitrate reductase disks. The percentage of correlation of 12 biochemicals using Minitek and 11 biochemicals using the API were compared with the Center for Disease Control reactions. The percentage of correlation of both positive and negative reactions with the API anaerobic strip ranged from 70.8 to 99.4% and with the Minitek from 97.1 to 100%. The microsystems were also evaluated as to the ease of use, adaptabilty to a clinical laboratory, time, and cost.